Preoperative Concentrated Urine Increases the Incidence of Plasma Creatinine Elevation After Major Surgery - Engel, Dominique; Löffel, Lukas M.; Wuethrich, Patrick Y.; Hahn, Robert G. (Frontiers in Medicine, 2021)
Background. Postoperative elevation of plasma creatinine is a frequent complication to major surgery. A rise by 50% fulfils the criterion for Acute Kidney Injury. We studied the relationship between concentrated urine before surgery, which is a sign of dehydration or chronically low intake of water, and the perioperative change in plasma creatinine. Methods. The creatinine concentration was measured in plasma and urine just before and at 6 h, 1 day, and 2 days after major abdominal surgery in a consecutive series of 181 patients. Receiver operating curve analysis was used to find the optimal cut-off to separate concentrated from diluted urine. Results. Plasma creatinine increased by > 25% in 50 patients (28%) and by > 50% in 22 patients (12%). Optimal cut-off for concentrated urine was urine creatinine of 11.3 mmol/L, which was exceeded in one third of the patients and associated with greater increase in plasma creatinine at 6 h (median 21% vs. 10%) and at 1 day postoperatively (21% vs. 7%; P< 0.0001). Elevation > 25% occurred in 41% and 19% in these two groups, respectively (P< 0.001) and an increase by > 50% in 16% and 10% (P=0.27). Patients with high urine creatinine before surgery failed to adequately concentrate their urine during the surgery, which is normally associated with intensified renal fluid conservation. Conclusion. High urinary concentration of creatinine before surgery should be considered as a risk factor for postoperative elevation of plasma creatinine. The mechanism is probably that the renal threshold is then more easily reached.